Systematic Literature Review: Implementasi Pendekatan Etnomatematika Pada Jenjang PAUD Di Indonesia - Wida Rachmiati (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2024)
The map of ethnomathematics research in Indonesia is still experiencing growth. Therefore, in Indonesia, studies related to ethnomathematics remain one of the interesting topics to explore. One of them is the implementation of ethnomathematics at the early childhood education (PAUD) level. The absence of data on articles demonstrating the implementation of ethnomathematics in the context of PAUD in previous research bibliometric analyses serves as the basis for this study. This research utilizes the systematic literature review (SLR) method to explore information regarding the distribution of articles on ethnomathematics topics at the PAUD level that have been published in online journals and proceedings. Data were collected from the Google Scholar database over the past 10 years. The results show that articles on ethnomathematics topics at the PAUD level appeared from 2017 to 2023. During this period, 8 articles were spread across 6 journals and 2 proceedings. Thus, on average, only 1 article on ethnomathematics topics at the PAUD level is published annualy. The research methods employed vary, including qualitative descriptive, ethnography, action research (PTK), mentoring, and quantitative methods. The results of this study indicate that ethnomathematics is highly likely to be applied at the PAUD level, but there are still very few researchers studying it.